Fatigue evaluation of rib-deck welds: Crack-propagation-life predictive model and parametric analysis. (October 2020) - Wang, Qiudong; Ji, Bohai; Li, Chuanxi; Fu, Zhongqiu
Abstract: The rib-deck welds in orthotropic steel decks are easily subjected to fatigue cracking under the coupled effect of welding residual stress, vehicle loads, structural geometry, etc. The root-deck crack, initiated at weld toe and propagated through the deck plate, is commonly detected in practical engineering. In this study, the crack propagation behavior of such crack geometry was estimated through a simplified predictive model for fatigue life based on the linear elastic fracture mechanics. The welding residual stress is simulated and reasonably considered. Fatigue testing data of five full-scale rib-deck welded specimens is extracted to validate the model. On this basis, parametric analysis is conducted to investigate the effect of welding residual stress, initial crack aspect ratio, loading amplitude and deck thickness. The results show that the proposed predictive model is acceptable for fatigue life estimation. The welding residual stress, averaged 152 MPa in the weld toe, has a considerable effect on the crack growth rate and the variation of crack aspect ratio. The crack propagation accelerates with the increase of the initial crack aspect ratio, indicating that the differences in the initial crack aspect ratio might be an important reason for the discreteness in fatigue tests. The decrease of loading amplitude considerably slows down the crack propagation, so is the increase of deck thickness. Graphical abstract: Unlabelled Image Highlights: Predictive model for crack propagation life is developed for rib-deck weld cracks. Fatigue testing data is extracted to validate the model. The distribution of welding residual stress is simulated and validated. Parametric analysis is conducted to evaluate the fatigue performance of rib-deck welds.